USP25 Expression in Peripheral Blood Mononuclear Cells Is Associated With Bone Mineral Density in Women - Shen, Jianlin; Fu, Bowen; Wu, Yanjiao; Yang, Yang; Lin, Xiaoning; Lin, Haibin; Liu, Huan; Huang, Wenhua (Frontiers in Cell and Developmental Biology, 2022)
Osteoporosis is the most common metabolic bone disease in postmenopausal women. As precursors of osteoclasts, peripheral blood mononuclear cells are accessible and considered suitable models for studying osteoporosis pathology. Ubiquitination is a crucial protein degradation system in bone metabolism. The aim of this study was to identify potential ubiquitination-related genes in PBMCs that are related to osteoporosis pathogenesis. Therefore, we performed an integrated analysis of osteoporosis-related microarray datasets. With the obtained ubiquitination-related gene set, weighted gene coexpression network analysis was performed. The results showed that genes in the turquoise module were correlated with menopause, and 48 genes were identified as hub genes. A differential expression analysis revealed 43 differentially expressed genes between pre- and postmenopausal samples. After integrating the information on differentially expressed menopause-related genes, we found that several members of the ubiquitin-specific protease (USP) family (USP1, USP7, USP9X, USP16, and USP25) were highly expressed in samples from postmenopausal female and that, USP25 expression was significantly higher in low-BMD samples than in high-BMD samples among samples from premenopausal subjects (p = 0.0013) and among all samples (p = 0.013). Finally, we verified the protein expression of USP25 in PBMCs by performing Western blot analysis, which yielded results consistent with the aforementioned results. Moreover, by assessing GTEx datasets, we found that USP25 expression was highly correlated with TRAF6 expression in whole blood (p < 0.001). We also tested the protein expression levels of TRAF6 in PBMCs and found that it was positively correlated with USP25 expression (p = 0.036). Our results reveal that the ubiquitin-specific protease family may play important roles in menopause and that USP25 is related to osteoporosis pathogenesis.